Trehalose Outperforms Chitosan, Humic Acid and Gamma-Aminobutyric Acid in Promoting the Growth of Field Maize - Li, Bingyan; Guo, Tengfei; Zhou, Wei (Frontiers in Plant Science, 2022)
Despite the fact that there are many distinct types of plant growth regulators (PGRs), the diverse ways in which they regulate plant development are rarely compared. In this study, four PGRs (trehalose, chitosan, humic acid and gamma-aminobutyric acid) were selected and sprayed folially, and plant samples were collected while maize was at vegetative leaf stages 6, 10 and 14 (V6, V10 and V14, respectively) to reveal the effects of different PGRs on photosynthesis, dry matter accumulation, oxidative stress, carbon and nitrogen metabolism, hormone levels, and gene expression of maize. Results showed that 100 mg/L PGRs did not induce oxidative damage or repair activities in maize. Trehalose significantly increased chlorophyll content at V6 and promoted dry matter (roots and shoots) accumulation at V6 and V10. The activities of carbon and nitrogen metabolizing enzymes were significantly enhanced by trehalose treatment, which promoted the accumulation of sucrose and soluble sugar, but did not affect the biosynthesis of auxin and gibberellin at V6. Changes in carbon and nitrogen metabolism enzymes are regulated by transcription of related synthetic genes. Lower starch content and higher sucrose content in trehalose-treated maize leaves are important biological characteristics. Further analysis revealed that the effect of trehalose on the metabolic activity of maize was a short-term promoting effect (0–12 d), while the effect on maize growth was a long-term cumulative effect (13–28 d). Overall, exogenous trehalose induced stronger carbon and nitrogen metabolic activity, higher photosynthetic capacity and more dry matter accumulation than chitosan, humic acid and gamma-aminobutyric acid.